2017
DOI: 10.1016/j.jacl.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of ApoA1 improve risk prediction of type 2 diabetes mellitus

Abstract: There is a high incidence of new T2DM at 8% over 4 years among Chinese. Larger BMI, higher glucose levels, and lower levels of ApoA1 are significantly and independently associated with new T2DM. Lower ApoA1 improves the risk prediction of new type 2 diabetes when it was added to the existing risk models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
(42 reference statements)
0
22
1
1
Order By: Relevance
“…In our study, we did not find any differences in HDL-c levels between patients with LDL-c within and above target. Low levels of ApoA1 also seem to independently associated with new T2DM (30). Nonetheless, according to the ESC/EAS guidelines, our patients evidenced normal ApoA1 concentrations and we did not find any differences in ApoA1 levels between patients with LDLc within and above target.…”
Section: Hdl-c and Apoa1mentioning
confidence: 40%
“…In our study, we did not find any differences in HDL-c levels between patients with LDL-c within and above target. Low levels of ApoA1 also seem to independently associated with new T2DM (30). Nonetheless, according to the ESC/EAS guidelines, our patients evidenced normal ApoA1 concentrations and we did not find any differences in ApoA1 levels between patients with LDLc within and above target.…”
Section: Hdl-c and Apoa1mentioning
confidence: 40%
“…The results are in line with previous studies where a significant decline in Apo A1 levels was observed in diabetics as compared to control group. [25] In a recent study carried out by Wu et al (2017) diminution in Apo A1 individually led to a 97% increased risk of new T2DM over 4 years among urban Chinese community based population who were healthy and without any risk factor for T2DM. [10] However, in a Turkish sample population elevated Apo A1 levels individually predicted the incidence of T2DM with top tertile of serum Apo A1 approximately doubled the possibility of T2DM when compared with low tertile.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In a recent study carried out by Wu et al (2017) diminution in Apo A1 individually led to a 97% increased risk of new T2DM over 4 years among urban Chinese community based population who were healthy and without any risk factor for T2DM. [10] However, in a Turkish sample population elevated Apo A1 levels individually predicted the incidence of T2DM with top tertile of serum Apo A1 approximately doubled the possibility of T2DM when compared with low tertile. [26] The present study demonstrated a significant increase in Apo B values in T2DM patients as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apolipoprotein A1 (APOA1), one type of apolipoprotein A family, is a primary protein component of highdensity lipoprotein (HDL) (7), and plays a role in reverse cholesterol transport that initiates multiple cellular pathways by binding to its receptor ABCA1 (8). Wu, X et al (9) reported that down-expressed APOA1 improves risk prediction of Type-2 diabetes mellitus. Tuft Stavnes, H et al reported that mRNA expression of APOA1 is a marker of longer survival in ovarian serous carcinoma effusions (10).…”
Section: Introductionmentioning
confidence: 99%